A Retrospective Evaluation of Laboratory Parameters and Hyperuricemia in Patients with Acne Vulgaris Under Systemic Isotretinoin Treatment - Sarac, Nalan; Pancar, Gunseli S.; Ozdemir, Sule; Atilla, Serra (Taylor & Francis Ltd, 2022)
Background Acne vulgaris is a chronic inflammatory disease affecting the pilosebaceous unit. Systemic isotretinoin (SI) is an effective, synthetic vitamin A derivative in the treatment of resistant acne or nodulocystic acne. This study aimed to investigate uric acid levels and laboratory parameters in patients receiving isotretinoin treatment. Materials and methods This study included 114 patients who were under SI treatment of 0.2-0.5 mg/kg/day aged between 17 and 44 years old. We retrospectively evaluated total cholesterol, triglyceride, aspartate aminotransferase (AST), alanine aminotransferase (ALT), urea, creatinine, creatinine kinase, uric acid, thrombocyte (Plt), and leucocyte (WBC) levels prior and on the fourth month of the treatment from the patients' records and compared these data statistically. Results The AST, creatinine kinase, cholesterol, triglyceride, and thrombocyte levels were significantly different (p<.001,p<.001,p<.001,p<.001, andp=.02, respectively), and no statistically significant differences were noted among the uric acid, creatinine, ALT, and WBC levels in the comparison of the baseline values and values at the fourth month of treatment (p>.05). Conclusions SI treatment of 0.2-0.5 mg/kg/day did not make significant alterations on serum uric acid levels. Besides, all alterations occurred within normal ranges.
Keywords: Acne; Isotretinoin; Hyperuricemia; Metabolic Syndrome